2004
DOI: 10.1111/j.1365-2354.2003.00441.x
|View full text |Cite
|
Sign up to set email alerts
|

An investigation of inpatient referrals to a clinical psychologist in a hospice

Abstract: A clinical psychologist, in a new post in a hospice, developed an assessment, therapeutic and consultation role. A retrospective, diary-based audit was made of the inpatients referred during the first 2 years, allowing an examination of referral practices and changes over time as the psychologist's role developed. During the 2 years 11% of the hospice inpatients were referred, consistent with previous published work in this area. Referrals increased from 10% in year 1 to 12% in year 2. Referrals were not skewe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
2

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 25 publications
0
7
0
2
Order By: Relevance
“…The clinical psychologists had multiple roles and functions in palliative care, 5,10 and the main focuses were patients and families. Many factors may influence the process of psychological care, but the underlying structure is similar.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The clinical psychologists had multiple roles and functions in palliative care, 5,10 and the main focuses were patients and families. Many factors may influence the process of psychological care, but the underlying structure is similar.…”
Section: Discussionmentioning
confidence: 99%
“…9 They can deal with various kinds of psychosocial issues, including emotional, psychosomatic, behavioral, and family problems. 10 A survey revealed that the most common psychological problems in terminal patients were depression, anxiety, and grief/bereavement, and that clinical psychologists were the first professionals that palliative care programs stated they would wish to hire. 11 However, there were not many clinical psychologists involved in palliative care in Europe in 2012.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Alexander (2004) conducted research in a hospice setting. His research demonstrated that younger patients were more often referred to his clinical psychology service than older people.…”
Section: Introductionmentioning
confidence: 99%
“…In many Western countries, particularly in the UK, the role of psychologists has developed as one of assessment, therapy and consulting, within their relatively new post in the hospice setting (4). Consequently, having a psychologist as part of the multidisciplinary team has enhanced the psychological component of palliative care within the hospice setting.…”
Section: Introductionmentioning
confidence: 99%